Method for Line Selection of Single-phase Arc Grounding Fault in Distribution Network Based on Extracting Fault Arc Characteristics. Issue 1 (1st January 2022) - Li, Shilong; Su, Xueneng; Gao, Yiwen; Long, Cheng; Yang, Yongbo
Abstract: Single-phase arc grounding fault is the most important fault form of the medium voltage in distribution network. Once the arc grounding fault occurs, the faulty point generates an arc, and the system generates an arc grounding over-voltage, so it is very necessary to analyze the faulty arc. The faulty arc current has obvious "zero rest phenomenon" at the zero point, and the voltage at this time rises suddenly. This characteristic can be used to analyze the fault. This paper analyzes the current of the faulty arc in MATLAB/Simulink, and extracts transient information of arc current through wavelet transform. According to the singular characteristics, the line selection is carried out by comparing the maximum value of the fourth scale of zero-sequence current of fault line and non-fault line under different "zero rest ratio". The result shows that the extraction of the arc feature is participating in the arc grounding fault to correctly select the fault line, and the principle is reliable, accurate and suitable for distribution networks in different grounding methods.